OP19 Fruit, vegetable, vitamin C intakes and plasma vitamin C: associations with insulin resistance in UK primary school children. (2nd September 2014) - Donin, AS; Dent, JE; Sattar, N; Owen, CG; Rudnicka, AR; Nightingale, CM; Stephen, AM; Cook, DG; Whincup, PH
Abstract : Background: Although high fruit and vegetable intakes and high vitamin C intake may protect against type 2 diabetes risk, recent evidence in adults has suggested that circulating vitamin C levels, rather than fruit and vegetable intake, could be particularly important. However, the influence of these factors on emerging type 2 diabetes risk in childhood (particularly insulin resistance) has not been reported. We therefore examined these associations in children, including their contributions to emerging ethnic differences in insulin resistance. Methods: This investigation is based on a cross-sectional, school-based survey in UK children aged 9–10 years, predominantly of white European, South Asian and black African origin from London, Birmingham and Leicester. Children provided a detailed 24-hour dietary recall (collected by a trained nutritionist) providing intakes of fruit, vegetables and vitamin C, had detailed measurements of body composition and provided a fasting blood sample for measurements of plasma vitamin C, serum insulin, plasma glucose, HbA1c and other metabolic markers; homeostasis model assessment (HOMA) insulin resistance was also derived. Multilevel linear regression models were fitted to provide adjusted means and differences in risk factors. Results: Among 2025 participants (68% response rate), intakes of fruit, vegetables and vitamin C showed no associations with markers of insulin resistance, though plasma vitamin C showed an inverse association. In age, gender, month, adiposity and school adjusted analyses, a 1 interquartile range increase in plasma vitamin C level was associated with 9.22% (95% CI 6.25, 12.11%) lower HOMA insulin resistance, 0.75% (95% CI 0.32, 1.18%) lower fasting glucose, a 4.11% (95% CI 2.78, 5.42%) lower urate and 2.26% (95% CI 1.03, 3.51%) higher HDL-cholesterol and (less consistently) a 0.62% (95% CI 0.24, 1.0%) higher HbA1c. Further adjustments for socio-economic status and physical activity did not substantially alter the results. Plasma vitamin C levels were markedly lower among South Asian children; higher levels of HOMA insulin resistance in South Asian children (particularly in Bangladeshis) could be at least partly accounted for (˜20%) by lower plasma vitamin C levels. Conclusion: Plasma vitamin C levels (but not fruit, vegetable or vitamin C intakes) are independently associated with insulin resistance in childhood, a consistent pattern to what has been shown in adult studies. Further studies are needed to establish whether this association is causal and can provide a basis for type 2 diabetes prevention.